2015
DOI: 10.1111/aje.12255
|View full text |Cite
|
Sign up to set email alerts
|

Do animal size, seasons and vegetation type influence detection probability and density estimates of Serengeti ungulates?

Abstract: Accurate detection of individual animals and estimation of ungulate population density might be a function of vegetation cover, animal size, observation radius or season. We assessed the effect of these factors on estimates of detection probability and density using five ungulate species in Western Serengeti National Park, Tanzania. Estimates were derived from information collected using ground surveys involving line transects targeting three resident species (impala, topi and buffalo) and two migrants (wildeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Conventional field sampling methods for estimating the occupancy (presence/absence) or abundance of focal organisms have often sought to determine the influence of seasonal activity or behavior on detection probabilities, and to incorporate this information into the design of effective surveys [ 27 , 28 ]. For example, studies of migratory species generally opt to sample for presence or abundance over windows of time when organisms are anticipated to be present (e.g., [ 29 , 30 ]), whereas studies of resident species often account for how seasonally varying factors like temperature or precipitation may influence detection probability as mediated through responses of organismal activity or behavior (e.g., [ 31 , 32 ]). Importantly, how season or temperature affects detection probability often differs by both species and sampling methodology [ 33 , 34 ], yet few studies to date have considered season as a factor that may influence detection probability of eDNA (but see [ 13 , 35 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional field sampling methods for estimating the occupancy (presence/absence) or abundance of focal organisms have often sought to determine the influence of seasonal activity or behavior on detection probabilities, and to incorporate this information into the design of effective surveys [ 27 , 28 ]. For example, studies of migratory species generally opt to sample for presence or abundance over windows of time when organisms are anticipated to be present (e.g., [ 29 , 30 ]), whereas studies of resident species often account for how seasonally varying factors like temperature or precipitation may influence detection probability as mediated through responses of organismal activity or behavior (e.g., [ 31 , 32 ]). Importantly, how season or temperature affects detection probability often differs by both species and sampling methodology [ 33 , 34 ], yet few studies to date have considered season as a factor that may influence detection probability of eDNA (but see [ 13 , 35 ]).…”
Section: Introductionmentioning
confidence: 99%
“…These earlier studies suggested that within each season, patterns of habitat selection differed between species, suggesting that species‐specific habitat preferences influence the distribution of each ungulate species across the Serengeti landscape. This occurs most prominently in three vegetation types: bush grassland, grassland and woodland (Anderson et al ., ; Bukombe et al ., ). Ndibalema () reported that grasslands, bush grassland and open woodland were the most heavily used vegetation types in western Serengeti.…”
Section: Discussionmentioning
confidence: 97%
“…The study area of 2490 km 2 is located between latitude 2° and 2°30″S and longitude 34° and 34°30″E (Figure ), in the western Serengeti ecosystem (Bukombe et al ., ). The elevation ranges from 1140 m west of Lake Victoria to 2000 m at the top of the Nyaroboro plateau (Jager, ).…”
Section: Methodsmentioning
confidence: 97%
“…The interactive effects of vegetation combined with distance from the line transect were of major importance for the detection of large Serengeti mammals [38], although survey speed was maintained at less than 10 km h −1 . This highlights the control of temporal covariates that affect detection probability via survey design, particularly where site-specific covariates are known to exert an influence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the two site-specific covariates of topography and habitat having little or no influence on detection probability in our study, it is still reasonable to expect that detection will vary in response to topography and habitat in other studies or areas. The interactive effects of vegetation combined with distance from the line transect were of major importance for the detection of large Serengeti mammals [38], although survey speed was maintained at less than 10 km h −1 . This highlights the control of temporal covariates that affect detection probability via survey design, particularly where site-specific covariates are known to exert an influence.…”
Section: Discussionmentioning
confidence: 99%